Human Mob1 proteins are required for cytokinesis by controlling microtubule stability - Florindo, Claudia; Schiebel, Elmar (Journal of cell science, 2012)
The completion of cytokinesis requires abscission of the midbody, a microtubule-rich cytoplasmic bridge that connects the daughter cells before their final separation. Although it has been established that both the midbody structure and membrane fusion are essential for abscission, the biochemical machinery and the cellular processes of abscission remain ill-defined. Here we report that human Mob1A and Mob1B proteins are involved in the regulation of abscission of the intercellular bridge. The Mob family is a group of highly conserved proteins in eukaryotes, described as binding partners as well as co-activators of protein kinases of the Ndr family, and as members of the Hippo pathway. We show that depletion of Mob1A and Mob1B by RNAi causes abscission failure as a consequence of hyper-stabilization of microtubules in the midbody region. Interestingly, depleting Mob1 also increases cell motility after cytokinesis, and induces prolonged centriole separation in G1 phase. In contrast, centrosomes fail to split when either Mob1A or Mob1B is overexpressed. Our findings indicate that human Mob1 proteins are involved in the regulation of microtubule stability at the midbody. We conclude that Mob1A and Mob1B are needed for cell abscission and centriole re-joining after telophase and cytokinesis.